Organizational Behavior Management (OBM) och feedback : En metod för konflikthantering - Lampa, Anders (2013)
A consultant, who works in Occupational health services in northern Sweden uses Organizational behavior management (OBM) in managing conflicts. The consultant describes the method as “it´s not the problem that is the problem, instead it´s the solution that is the problem”. OBM does not focus on what has happened and what employees feel, but on behavior, that is what employees do and say in a given situation. Are OBM and feedback effective methods for conflict management? The results of a literature review show, that if the organization can identify and pinpoint behavior in combination with feedback and rewards, performance may be increased and the organization may achieve enhanced targets. However, the results also show a significant lack of research on the effects of OBM and feedback on conflict solution in a work place. Validerat; 20130828 (global_studentproject_submitter)